2021
DOI: 10.1044/2021_jslhr-20-00640
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility, Articulation Rate, Fluency, and Communicative Efficiency in Typically Developing Children

Abstract: Purpose This article describes the developmental trajectories of four communication-related parameters (i.e., intelligibility, articulation rate, fluency, and communicative efficiency) in a cross-sectional study of typically developing children between 3 and 9 years. The four target parameters were related to auditory-perceptual parameters of speech function. Method One hundred forty-four typically developing children (ages 3;0–9;11 [years;months]; 72 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Notably, recent research suggested that speech intelligibility is still developing for many typically developing children beyond 9 years of age. 27,28 Similarly, studies of speech intelligibility growth in children with CP suggested a very protracted time course, 29 with periods of most rapid growth occurring more than a year later than expected for typical peers. 30,31 Given this growth lag and the protracted course of development among children with and without speech motor impairment, it is important to understand how developmental change translates to ordinal rating scale classification on the VSS and the extent to which early ratings are predictive of later ratings.…”
Section: Longitudinal Speech Classification In Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, recent research suggested that speech intelligibility is still developing for many typically developing children beyond 9 years of age. 27,28 Similarly, studies of speech intelligibility growth in children with CP suggested a very protracted time course, 29 with periods of most rapid growth occurring more than a year later than expected for typical peers. 30,31 Given this growth lag and the protracted course of development among children with and without speech motor impairment, it is important to understand how developmental change translates to ordinal rating scale classification on the VSS and the extent to which early ratings are predictive of later ratings.…”
Section: Longitudinal Speech Classification In Cpmentioning
confidence: 99%
“…However, speech development differs from other motor development domains. Notably, recent research suggested that speech intelligibility is still developing for many typically developing children beyond 9 years of age 27,28 . Similarly, studies of speech intelligibility growth in children with CP suggested a very protracted time course, 29 with periods of most rapid growth occurring more than a year later than expected for typical peers 30,31 .…”
mentioning
confidence: 99%
“…Recent research has provided foundational knowledge on speech intelligibility growth trajectories based on transcription intelligibility methods for children between the ages of 2 and 10 years ( Hustad et al, 2020 , 2021 ; Schölderle et al, 2021 ). Transcription intelligibility measures involve recording speech samples from a child, preparing a master transcript of the target words or utterances produced by the child, and having naïve listeners orthographically transcribe the speech recording.…”
Section: Transcription Intelligibilitymentioning
confidence: 99%
“…Until very recently, comprehensive normative standards for characterizing intelligibility development in typical children did not exist. The most recent work, however, has provided a foundation for understanding growth trajectories between the ages of 2 and 10 years [ 8 , 9 , 10 ]. Results have indicated that children’s intelligibility grows rapidly in the preschool years and is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Results have indicated that children’s intelligibility grows rapidly in the preschool years and is highly variable. Intelligibility continues to improve with age throughout middle childhood, and variability decreases with age [ 8 , 9 , 10 ]. Studies of typical speech intelligibility development provide an important foundation for interpreting intelligibility in children with dysarthria.…”
Section: Introductionmentioning
confidence: 99%